Analisis motivasi belajar matematika siswa melalui media google meet terhadap kemampuan pemahaman konsep matematis siswa di masa pandemi COVID-19 - Islami Nur, Fadillah; Kusumo, Sri Wibowo (International Journal of Progressive Mathematics Education, 2024)
Purpose: This study evaluates the correlation between learning motivation, self-regulation, and the use of Google Meet in enhancing students' mathematical concept understanding of systems of linear equations (SPLDV).Design/methodology/approach: A quantitative correlational design was employed with 32 students at SMPN 4 Tambun Selatan. Data were collected via the Mathematics Attitudes and Perceptions Survey (MAPS), self-regulation inventories, and concept mastery tests, then analyzed using Bayesian estimation and regression.Findings: Findings reveal a significant positive correlation ($r = 0.78$) between motivation and concept mastery. Motivation and self-regulation contribute 61% to learning outcomes, while synchronous interaction via Google Meet effectively mitigates mathematics anxiety and fosters creative thinking.Practical implications: Educators should integrate synchronous feedback and independent study workbooks to optimize spaced retrieval practice, ensuring long-term knowledge retention in digital environments.Originality/value: This research contributes to the literature by synthesizing psychological dispositions with synchronous technology, validating the "expert-like views" model within middle-school online mathematics education.     Purpose: Penelitian ini mengevaluasi korelasi antara motivasi belajar, kemandirian belajar, dan penggunaan Google Meet dalam meningkatkan pemahaman konsep matematis siswa pada materi Sistem Persamaan Linear Dua Variabel (SPLDV). Design/methodology/approach: Desain kuantitatif korelasional digunakan terhadap 32 siswa SMPN 4 Tambun Selatan. Data dikumpulkan melalui Mathematics Attitudes and Perceptions Survey (MAPS), inventori kemandirian, dan tes penguasaan konsep, lalu dianalisis menggunakan estimasi Bayesian dan regresi. Findings: Hasil menunjukkan korelasi positif signifikan (r = 0,78) antara motivasi dan penguasaan konsep. Motivasi dan kemandirian berkontribusi 61% terhadap hasil belajar, sementara interaksi sinkronus via Google Meet efektif memitigasi kecemasan matematis dan mendorong berpikir kreatif. Practical implications: Pengajar harus mengintegrasikan umpan balik sinkronus dan buku kerja mandiri untuk mengoptimalkan spaced retrieval practice, menjamin retensi pengetahuan jangka panjang di lingkungan digital. Originality/value: Penelitian ini berkontribusi pada literatur dengan menyintesis disposisi psikologis dan teknologi sinkronus, memvalidasi model "pandangan menyerupai ahli" dalam pendidikan matematika daring tingkat sekolah menengah.